Evaluation of completeness and timeliness of data in the National Information System for Notifiable Diseases for spotted fever in the state of São Paulo, Brazil, 2007-2017 - Xavier, Daniele Rosa (2023)
Objective: To evaluate the completeness and timeliness of notifications of cases of spotted fever (SF) in the National System of Information on Notifiable Diseases (Sinan) in the state of São Paulo, from 2007 to 2017. Methods: This is a descriptive and ecological study of confirmed human cases of SF for completeness and timeliness of ten form fields (good if ≥ 90% for most variables). Linear regression was performed to analyze trends in the time series. Results: Among essential fields, only “Discharge date” showed low completeness (68.5%). “Investigation” and “Closure” had good timeliness; other intervals were not adequate. Conclusion: In the state of São Paulo, data completeness was good for most variables, but not adequate in terms of timeliness, except for “Closing” and “Investigation”, pointing to the need for health education and communication actions on SF.